2020
DOI: 10.3311/ppci.16664
|View full text |Cite
|
Sign up to set email alerts
|

Impact Response of Hammerhead Pier Fibrous Concrete Beams Designed with Topology Optimization

Abstract: Reducing the weight of concrete beams is a primary (beyond strength and durability) concern of engineers. Therefore, this research was directed to investigate the impact response of hammerhead pier concrete beams designed with density-based method topology optimization. The finite element topology optimization was conducted using Autodesk fusion 360 considering three different mesh sizes of 7 mm, 10 mm, and adaptive meshing. Three optimized hammerhead beam configurations; HB1, HB2, and HB3, respectively, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 60 publications
1
21
0
Order By: Relevance
“…Previous studies that used steel fiber, polypropylene fiber and other synthetic fibers revealed a distinguished superiority of steel fibers, both in mono-fashion or when combined with synthetic fibers, where it could better improve the stiffness, tensile strength, flexural strength, ductility, shear strength and energy absorbance capacity [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ], which totally supports the obtained results in this research. Scorza et al [ 44 ] tested different combinations of different length steel and polypropylene fibers and indicated that steel mono-fiber reinforced mixture retained the best fracture results and post-peak performance under mode I fracture test.…”
Section: Resultssupporting
confidence: 90%
“…Previous studies that used steel fiber, polypropylene fiber and other synthetic fibers revealed a distinguished superiority of steel fibers, both in mono-fashion or when combined with synthetic fibers, where it could better improve the stiffness, tensile strength, flexural strength, ductility, shear strength and energy absorbance capacity [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ], which totally supports the obtained results in this research. Scorza et al [ 44 ] tested different combinations of different length steel and polypropylene fibers and indicated that steel mono-fiber reinforced mixture retained the best fracture results and post-peak performance under mode I fracture test.…”
Section: Resultssupporting
confidence: 90%
“…Consequently, changing the direction of cracks due to fibre-bridging action leads to delays in crack growth and failure [25,26]. In general, the percentage of SF in conventional fibrous concrete is restricted to 2% due to fibre balling, which creates poor fibre distribution and more internal flaws, leading to reduced compressing strength [27,28]. However, this kind of problem was eradicated in TECAFC since ECA and fibres were premixed and filled into the empty mould before grout injection [29,30].…”
Section: Compressive Strengthmentioning
confidence: 99%
“…Figure 14 shows the process of damage resulting in the above-stated effects, including localized damages at the point of contact between the steel load transmission rod and the specimen. Transverse shear stress/strain led to delamination of the inner structure [ 88 ]. Tensile-wave transfer upon impact caused the matrix and fibres to debond into the surrounding areas, produced by tensile and compressive bending on the bottom and top surfaces, respectively.…”
Section: Discussion Of Resultsmentioning
confidence: 99%